Implementation of two way Quantum Key Distribution protocol with decoy state - Mohd Fared Abdul Khir; M. N. Mohd Zain; Iskandar Bahari; Suryadi; S. ShaarI (Elsevier, 2024)
Optics Communications Volume 285, Issue 5, 1 March 2012, Pages 842-845